Намисто з Чорнівського городища ХІІІ ст. (дослідження 1999—2020 рр.) - Калініченко, В.А.; Пивоваров, С.В. (Археологія і давня історія України, 2022)
Під час археологічних робіт на Чорнівському городищі виявлено різноманітні прикраси, якими оздоблювався повсякденний і святковий одяг представниць
жіночої статі, які мешкали на території феодального замку в першій половині — середині ХІІІ ст.
Матеріал з якого вони зроблені, типологія та технологія виробництва дозволяють говорити, що конкретні прикраси могли належати різним соціальним, етнічним і віковим групам місцевих жительок.
Під час дослідження городища виявлено 72 екземпляри цілих і фрагментованих намистин. Вони представлені: виробами з металу — еліпсоподібними намистинами прикрашеними філігранню й зерню,
ажурними каркасними намистинами оздобленими
зерню, фігурною намистиною; мушлями каурі; скляними виробами — монохромними, поліхромними та
із металевою фольгою намистинами. During the archeological works on the Chornivka
hillfort various ornaments which decorated the everyday
and festive clothes of women having lived on
the territory of the feudal castle in the first half —
the mid-13th century were discovered. The material
from which they are made, typology and production
technology suggest that definite jewelry could belong
to different social, ethnic and age groups of local
people.
The old Ukrainian women’s necklaces and breast
adornment in addition to aesthetic function also had
protective and social ones. These categories include a
number of necklaces with numerous pendants. Their
form and ornamentation reflected the local population
worldviews, where together with Christian symbols,
pagan elements were used. All of this shows the combination
in these ornaments the primitive and Christian
principles and the syncretism of their semantic
content.
One of the most numerous groups of women’s breast
ornaments from the hillfort is a necklace. Most of the
beads are represented by single finds but their clusters
(minithesaurus) have also been recorded.
During the study of the hillfort 72 whole and fragmented
beads were found. They are represented by
metal items such as elliptical beads decorated with
filigree and grain, openwork frame beads decorated
with grain, figured beads; cowrie shells; glass items —
monochrome, polychrome and beads with metal
foil.
The beads found on the hill-fort significantly increase
the information on the elements of old Ukrainian
women’s costume decoration in the region and allow
tracing the trade, economic, cultural and possibly
military and political ties of the feudal castle in the
first half — the mid-13th century.